2015
DOI: 10.1371/journal.pone.0142081
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Study of SRT2104, a SIRT1 Activator, in Patients with Moderate to Severe Psoriasis

Abstract: Activation of Sirtuin (silent mating type information regulation 2 homolog) 1, or SIRT1, is an unexplored therapeutic approach for treatment of inflammatory diseases. We randomized 40 patients with moderate-to-severe psoriasis (4:1) to three escalating doses of SRT2104, a selective activator of SIRT1, or placebo. Across all SRT2104 groups, 35% of patients (p<0.0001) achieved good to excellent histological improvement based on skin biopsies taken at baseline and day 84 but was not consistently in agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 18 publications
(23 reference statements)
1
60
0
Order By: Relevance
“…Currently, given the promising results in patients with psoriasis treated with SRT2014 (REF. 131), further clinical trials for this disease seems to be a good path to follow. Compounds that raise NAD + levels, such as nicotinamide riboside and NMN, also show great promise as calorie restriction mimetics to treat numerous age-related conditions, and possibly extend lifespan.…”
Section: Future Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, given the promising results in patients with psoriasis treated with SRT2014 (REF. 131), further clinical trials for this disease seems to be a good path to follow. Compounds that raise NAD + levels, such as nicotinamide riboside and NMN, also show great promise as calorie restriction mimetics to treat numerous age-related conditions, and possibly extend lifespan.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…A separate study of patients with the inflammatory condition plaque-type psoriasis showed a significant reduction in disease manifestation following 84 days of oral administration of 500 or 1,000 mg per kg SRT2104 (REF. 131). Pharmaceutical companies are continuing to develop STACs that have improved pharmaceutical properties and to conduct additional clinical trials (J. Ellis, personal communication).…”
Section: Sirtuin-activating Compoundsmentioning
confidence: 99%
“…Furthermore, only male animals were performed in this study, and whether septic female mice will also benefit from SRT1720 treatment requires further evaluation. Other STACs, like SRT2140, have been in phase II clinical trials for the treatment of patients with moderate to severe psoriasis 45 and type 2 diabetes. 46 The majority of adverse events in these clinical trials were mild to moderate in severity and self-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently reported adverse events in the SRT2104 arms were: dizziness, headache, psoriatic arthropathy, gastrointestinal symptoms and transaminase elevations. 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…Its activation via resveratrol has been shown to improve psoriasis in humans [60] and an induced psoriasis-like inflammation in mice [61]. SIRT1 is downregulated in systemic sclerosis and likely plays a role in the regulation of fibroblast activation in the disease via TGF-P signaling [62, 63].…”
Section: Introductionmentioning
confidence: 99%